The use of soy protein isolate in meatballs and its effect on the quality and shelf life of the product - Joko Hermanianto; Dhita Sari; Nugraha Edhi Suyatma (Hasanuddin University Food Science and Technology Study Program, 2021)
Beef meatballs are in great demand by the public because of their non- porous texture, juicy, and chewy characteristics, as well as their ability to be stable at cooking temperatures with a long shelf life. The use of Isolated Soy Protein (ISP) shapes the character of meatballs because of its functional properties, including good water holding capacity and emulsion stability formation in a mixture of processed meat products. This research aims to technically determine the multiple emulsion properties of ISP at doses of 0%, 2%, 4%, and 8% and obtain a meatball formulation with a long shelf life that suits the target consumer. The tests include the ISP emulsification, meatball peel formation, product stability, Arrhenius shelf life method, and the sensory evaluation of the hedonic test. Subsequently, data were processed in a completely randomized 1x5 and a 4x3 factorial design using SPSS. The emulsification properties of ISP were determined by producing OE (Oil Emulsion) and PG (Purine Gel). Furthermore, ISP was discovered to change the percentage of meat consumed by approximately 2% as the characteristics of meatball products desired by consumers were achieved. The best formulation of meatballs was achieved with 2% dry ISP in the first mixing and was conducted at a boiling point of 65°C